Study of hematological and biochemical parameters in a cohort of Indian COVID-19 patients admitted in a tertiary care centre - Agrawal, Abhishek; Tyagi, Princy; Mahavar, Sunil; Banerjee, Subrata; Sharma, Raman; Bhandhari, Sudhir; Keswani, Prakash (International Journal of Advances in Medicine, 2020)
Background: In this study authors retrospectively analyzed the record of 102 patients with confirmed COVID-19 infection to determine factors associated with severity of disease. Methods: Clinical, biochemical, radiological and hematological profiles of 102 patients with confirmed SARS-CoV-2 RNA testing were obtained and analyzed. Results: A total of 102 patients were enrolled, with median age of patients of 32.5 years (range 10-85 years), of which 83.3% (85/102) were asymptomatic and 16.67% (17/102) symptomatic. Eighteen (17.6%) patients had co-existing illnesses. Clinical spectrum among COVID-19 patients varied from being asymptomatic to having symptoms like fever, dry cough, breathlessness with few progressing to respiratory failure and multi-organ failure. In our study, 97.05% (99/102) recovered while 2.94% (3/102) died. Mean age, total leucocyte count (TLC), neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and lactate dehydrogenase (LDH) of severely ill patients were significantly higher than those of patients with non-severe illness. Conclusions: Elevated NLR, TLC, PLR, LDH and lymphopenia were seen in the symptomatic patients especially manifesting severe disease. Early intervention and periodic monitoring of these parameters in patients, especially with severe disease may help in improving disease outcome.